Evaluation Of The Accounts Receivable Collection System For Goods Deliveries At PT. Pos Indonesia (Persero) Gunungsitoli Branch - Telaumbanua, Rinaldi Emmanuel; Waruwu, Noviza Asni; Serniati Zebua; Kurniawan Sarototonafo Zai (Journal of Management, Economic, and Accounting, 2025)
This research, entitled “Evaluation of the Accounts Receivable Collection System for Goods Delivery at PT Pos Indonesia (Persero) KC Gunungsitoli”, aims to evaluate the effectiveness of the receivables collection system, identify the obstacles encountered, and provide recommendations for improvement to enhance receivables collectibility and maintain the company’s cash flow stability. The research method used is descriptive qualitative, with data collected through interviews, documentation, and literature studies. The results show that the collection procedure has a clear workflow, starting from transaction recording, monthly recapitulation, preparation of billing documents, and invoice delivery to partners at the beginning of each month. However, the implementation still faces several challenges, including late payments from partners due to internal administrative issues, the absence of late payment penalties or incentives for early payment, and the suboptimal use of technology such as the automatic reminder feature in SAP. Based on these findings, this study recommends implementing an integrated digital collection system, improving collection policies, increasing the intensity of communication with partners, strengthening real-time receivables monitoring, and enhancing staff competencies in collection management. By applying these measures, the company is expected to improve the effectiveness of its receivables collection system, accelerate cash turnover, and reduce the risk of uncollectible accounts.